A combined deficiency of tissue factor and PAR-4 is associated with fatal pulmonary hemorrhage in mice. Issue 146 (October 2016) - Bode, Michael F.; Mackman, Nigel
Abstract: Introduction: Mice with a complete absence of tissue factor (TF) die during embryonic development whereas mice with low levels of TF (Low-TF mice) survive to adulthood. Low-TF mice exhibit spontaneous hemorrhage in various organs, including the lung. In contrast, mice can survive without protease-activated receptor (PAR)-4, which is the major thrombin receptor on mouse platelets. We determined the effect of combining a deficiency PAR-4 (primary hemostasis) with a deficiency in TF (secondary hemostasis) on embryonic development and survival of adult mice. Materials and methods: Low-TF mice (mTF −/−, hTF +/+ ) were crossed with PAR-4 −/− mice to generate heterozygous mice (mTF +/−, hTF +/−, PAR-4 +/− ). These mice were intercrossed to generate Low-TF mice lacking PAR-4. Mice surviving to wean were genotyped and survival was monitored for 6 months. Results: We observed the expected number of Low-TF, PAR-4 −/− mice at wean indicating survival in utero and after birth. However, an absence of PAR-4 was associated with premature death of all Low-TF, PAR-4 −/− mice in the 6 month observational period. This compares with 40% death of the Low-TF, PAR-4 +/+ mice (p = 0.003). Low-TF, PAR-4 +/− mice had an intermediate phenotype with 55% of the mice dying within 6 months. The primary cause of mortality of Low-TF, PAR-4 −/− mice was pulmonary hemorrhage. Conclusions: Low-TF, PAR-4 −/− mice survive into adulthood, but combining a deficiency of primary hemostasis (PAR-4 deficiency) with secondary hemostasis (low levels of TF) leads to premature death primarily due to pulmonary hemorrhage. Highlights: Mice with a deficiency of TF and PAR-4 survive to wean. Combining low levels of TF with a deficiency of PAR-4 leads to premature death. The primary cause of death of Low-TF, PAR-4 −/− mice is pulmonary hemorrhage.